The association of perirenal adipose tissue accumulation with left ventricular hypertrophy and the mediating role of insulin resistance: a cross-sectional study involving 1112 individuals with type 2 diabetes mellitus - Wang, Wei; Chen, Yang; Qiu, Xiu Ping; Guo, Xiu Li (Frontiers in Endocrinology, 2025)
ObjectiveRecent studies have underscored the metabolic and cardiovascular regulatory capacity of perirenal adipose tissue (PAT), implicating its potential involvement in the pathogenesis of left ventricular hypertrophy (LVH). This investigation aims to assess the relationship between increased PAT mass and LVH, while also examining the potential mediating role of insulin resistance in this relationship among individuals with type 2 diabetes mellitus (T2DM).Method1112 individuals with T2DM were prospectively recruited for this study. Perirenal fat thickness (PrFT), measured using unenhanced abdominal CT, served as a measure of PAT mass. The triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-c) was computed to assess insulin resistance. LVH was identified as left ventricular mass index (LVMI) >115 g/m² in men or LVMI >95 g/m² in women. The correlations of LVH risk with PrFT and TG/HDL-c were analyzed by weighted binomial logistic regression and restricted cubic splines (RCS) analyses. Furthermore, the mediating role of TG/HDL-c in this relationship was explored using the adjusted mediation analysis.ResultsParticipants in the LVH group displayed significantly higher PrFT and TG/HDL-c than the non-LVH group (P < 0.001). Adjusting for confounding factors, the LVMI demonstrated a positive correlation with PrFT (β=0.262, P<0.001) and TG/HDL-c (β=0.206, P<0.001). PrFT and TG/HDL-c emerged as independent variables for LVH, with odds ratios of 1.33 (95%CI:1.24-1.43, P<0.001) and 1.20 (95%CI:1.05-1.36, P=0.006), respectively. Each standard deviation increases in PrFT and TG/HDL-c conferred an additional 240% (P<0.001) and 41% (P=0.006) risk for LVH. A linear correlation of LVH risk with PrFT and TG/HDL-c was observed from RCS analysis (P for nonlinear and overall< 0.001). Moreover, TG/HDL-c mediated 13.4% of the association between PrFT and LVMI, and 8.5% between PrFT and LVH.ConclusionIncreased PAT accumulation contributes to an independent variable for LVH, with insulin resistance acting as a mediating variable in this relationship.